DNA Methylation Analysis of Ribosomal DNA in Adults With Down Syndrome - Ravaioli, Francesco; Zampieri, Michele; Morandi, Luca; Pirazzini, Chiara; Pellegrini, Camilla; De Fanti, Sara; Gensous, Noémie; Pirazzoli, Gian Luca; Sambati, Luisa; Ghezzo, Alessandro; Ciccarone, Fabio; Reale, Anna; et al. (Frontiers in Genetics, 2022)
Control of ribosome biogenesis is a critical aspect of the regulation of cell metabolism. As ribosomal genes (rDNA) are organized in repeated clusters on chromosomes 13, 14, 15, 21 and 22, trisomy of chromosome 21 confers an excess of rDNA copies to persons with Down Syndrome (DS). Previous studies showed an alteration of ribosome biogenesis in children with DS, but the epigenetic regulation of rDNA genes has not been investigated in adults with DS so far. In this study we used a targeted deep-sequencing approach to measure DNA methylation (DNAm) of rDNA units in whole blood from 69 adults with DS and 95 euploid controls. We further evaluated the expression of the precursor of ribosomal RNAs (RNA45S) in peripheral blood mononuclear cells (PBMCs) from the same subjects. We found that rDNA promoter tends to be hypermethylated in DS with respect to the control group. The analysis of epihaplotypes (the combination of methylated and unmethylated CpG sites along the same DNA molecule) showed a significantly lower intra-individual diversity in the DS group, which at the same time was characterized by a higher inter-individual variability. Finally, we showed that RNA45S expression is lower in adults with DS. Collectively, our results suggest a rearrangement of the epigenetic profile of rDNA in DS, possibly to compensate for the extranumerary rDNA copies. Future studies should assess whether the regulation of ribosome biogenesis can contribute to the pathogenesis of DS and explain the clinical heterogeneity characteristic of the syndrome.